Cases of detection of serotype 14 bluetongue vaccine-like virus in the RF and European countries in 2011-2012 - V. M. Zakharov; A. V. Kononov; V. A. Mischenko (Ветеринария сегодня)
Associated with isolation of vaccine-like attenuated bluetongue virus cases of 14 serotype bluetongue virus detection in European countries and the RF in 2011 -2012 are analysed in the paper.